2021
DOI: 10.21873/anticanres.15222
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve of Robotic-assisted Hysterectomy With Pelvic Lymphadenectomy for Early Stage Endometrial Cancer: Analysis of 81 Cases

Abstract: Background/Aim: The purpose of this study was to evaluate the learning curve of robotic hysterectomy and pelvic lymphadenectomy for early-stage endometrial carcinoma. Patients and Methods: A retrospective chart review was performed on the first 81 surgeries performed by a single surgeon. The 81 cases were divided into three groups; 4 subgroups of 20 cases each, 3 subgroups of 27 cases each, and 2 subgroups of 40 cases each. The surgical outcomes in each group were analyzed, using operative time, estimated bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, robot-assisted surgery is also indicated for benign uterine myoma, and in the United States, the gynecological department comprised the largest number of robot-assisted surgery [3,4]. Some papers have reported that the learning curve for robotassisted surgery requires 20 to 30 cases for significant improvement in many departments, including gynecology and urology [5][6][7]. On the other hand, Hwang et al [8] and Chong et al [9] reported that the learning curve for laparoscopic surgery for gynecologic malignancies is generally 35 and 50 cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, robot-assisted surgery is also indicated for benign uterine myoma, and in the United States, the gynecological department comprised the largest number of robot-assisted surgery [3,4]. Some papers have reported that the learning curve for robotassisted surgery requires 20 to 30 cases for significant improvement in many departments, including gynecology and urology [5][6][7]. On the other hand, Hwang et al [8] and Chong et al [9] reported that the learning curve for laparoscopic surgery for gynecologic malignancies is generally 35 and 50 cases, respectively.…”
Section: Discussionmentioning
confidence: 99%